Potential use of microbial product to degrade Chlorpyrifos in tea cultivation soil - Thi Thanh Xuyen, Duong; Huu Thanh, Luong; Ngoc Quynh, Nguyen; Thuy Nga, Vu; Trong Anh, Dam; Thanh Lam, Nguyen; Bang Tam, Nguyen Kieu (VNU Journal of Science: Earth and Environmental Sciences, 2024)
Pesticides containing organophosphate (OP) compounds in general and Chlorpyrifos   (CPF) in particular are used to control insects and pests. However, they have been proven to be highly toxic not only to some insects and wild animals but also have negative impacts on the environment and human health. This study provides an assessment of the effectiveness of using microbial product (MP) to degrade CPF in a large- and small-scale tea cultivation environment. The research results show that in some farming areas, residual CPF exists both in the soil and in agricultural products. When using the MP, the CPF content in tea decreased by 77.66%; the efficacy of CPF treatment in the soil reached 72-76% in the small scale . Additionally, the use of MP also increased the total microbial density in the net house scale from 10 6 to 10 7 CFU/g and beneficial microorganisms in the soil, stimulating growth and productivity for tea plants.